Manual Pipe Beveling Machine: An Innovative Technology Research in Preparing Weld Materials - Mateo A. Alin Jr.; Jose P. Magallanes; John Ayan L. Euldan; Alan A. Bendanillo (Science and Education, 2024)
This innovative technology research addresses the need of the trainees to improve and develop their common competencies, specifically how to prepare weld materials as a prerequisite to the core competency. Further, it also responded to the issues and concerns of the Regional Training Center - Cebu in relation to the cross-cutting measures implemented to reduce the power consumption generated during the training. The descriptive survey method of research and document review were used in this research. To gather the needed data from the respondents/Trainees, a survey questionnaire was formulated. In addition, the data were analyzed and interpreted using percentage, weighted mean, and frequency; chi-square was utilized to determine whether a difference was significant. The data revealed that out of 50 SMAW Trainees for the two batches, the majority ranged from 22-27 years of age or 45 percent of the overall respondents and considered millennial trainees. It was then followed by another set of age ranged from 28- 33 years of age or 25 percent of the respondents which also considered belong to millennial generation and followed by another set of age ranged from 34-39 or 15 % of the respondents which are belong also to generation x learners. Further, 1 or 5 percent of the remaining respondents fell on the age ranged from 40-45 years of age, which is considered as the Generation X Trainees. This implies that the majority of the respondents belong to the millennial generation. The data showed a substantial correlation between the group respondents' SMAW abilities and their profile. The P value exceeded the significance threshold. This suggests that the respondents' profiles directly influence the competences of the group respondents. It was determined that there needed to be more common and core competency knowledge among the group responders. Thus, there is still a need to improve their skills and knowledge in the Shielded Metal Arc Welding qualification. Further, the issues and concerns regarding the cross-cutting measure were also responded to because it revealed a significant decrease in the total power bill consumption over the two consecutive years of monthly monitoring. Therefore, it is highly recommended to fabricate another unit of this Manual Pipe Beveling Machine to maintain the savings and help reduce the power consumption generated by the SMAW qualification.